Injection molding composition, method for producing injection molded body, and method for producing titanium sintered body

By using a mixture of ceramic powder and titanium-based powder in the MIM method and adjusting the particle size and content of the ceramic powder, the problem of uneven mixing of titanium powder and organic binder is solved, and the surface quality and aesthetics of the injection molded body are significantly improved.

JP7666119B2Active Publication Date: 2025-04-22SEIKO EPSON CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021083697
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-18
Publication Date
2025-04-22
Estimated Expiration
2041-05-18

AI Technical Summary

Technical Problem

In the metal powder injection molding (MIM) method, the titanium powder is unevenly mixed with the organic binder, resulting in uneven distribution of the binder in the injection molded body, resulting in the problem of degradation of surface quality and reduced aesthetics.

Method used

A mixture of titanium-based powder and ceramic powder is used as the injection molding material, wherein the average particle size of the ceramic powder is between 1 nm and 100 nm, and the mass fraction of the ceramic powder is between 0.01% and 0.30%. By adjusting the particle size and content of the ceramic powder, the flowability and mixing uniformity between the powders are improved.

Benefits of technology

Through the intervention of ceramic powder, the mixing uniformity of the titanium-based powder and the organic binding agent is improved, the uneven distribution of the binding agent is reduced, the surface quality and aesthetics of the injection molded body are significantly improved, and the defects in the injection molding process are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666119000004
    Figure 0007666119000004
  • Figure 0007666119000005
    Figure 0007666119000005
  • Figure 0007666119000006
    Figure 0007666119000006
Patent Text Reader

Abstract

To provide an injection molding composition capable of forming an injection molded body with reduced molding defects due to the uneven distribution of an organic binder as well as improved surface properties, and a method for producing an injection molded body using the injection molding composition, and a method for producing a titanium sintered body.SOLUTION: An injection molding composition contains a titanium-based powder containing titanium as a main component and having an average particle diameter of 15 μm or more and 35 μm or less, a ceramic powder containing ceramic as a main material and having an average particle diameter of 1 nm or more and 100 nm or less, and an organic binder. The ceramic is oxide-based ceramic containing an oxide as a main component, and a standard free energy of formation of the oxide at 1000°C may be lower than a standard free energy of formation of titanium oxide at 1000°C.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an injection molding composition, a method for producing an injection molded article, and a method for producing a titanium sintered article. [Background technology]

[0002] Titanium alloys have excellent mechanical strength, corrosion resistance, and a low Young's modulus, and are therefore used in a variety of fields, including aircraft, space development, chemical plants, exterior parts for wristwatches, ornaments such as eyeglass frames, and sporting goods such as golf clubs.

[0003] In manufacturing such parts, powder metallurgy can be used to easily manufacture titanium sintered bodies with shapes close to the final shape, which makes it possible to omit or reduce the amount of secondary processing, enabling efficient part production.

[0004] For example, Patent Document 1 discloses a method for manufacturing hairdressing scissors, which includes the steps of obtaining an injection molded body by metal powder injection molding (MIM) using a molding material containing a metal powder made of precipitation hardened stainless steel and an organic binder, degreasing the injection molded body to obtain a degreased body, and sintering the degreased body to obtain a sintered body. This method makes it possible to manufacture hairdressing scissors using precipitation hardened stainless steel, which has been thought to be unsuitable for hairdressing scissors because of its too high Rockwell hardness. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-142594 A Summary of the Invention [Problem to be solved by the invention]

[0006] In this type of MIM method, in order to improve the quality of the final sintered body, it is important that the metal powder and organic binder are mixed uniformly in the molding material. However, titanium powder made of titanium or titanium-based alloys has the property of being difficult to mix uniformly with the organic binder. This makes it easy for the organic binder to become unevenly distributed in the molding material. In particular, the organic binder tends to be unevenly distributed in areas where the wall thickness changes suddenly and near the gate of the mold.

[0007] When the organic binder is unevenly distributed, the balance between the titanium powder and the organic binder is lost in that area, and the organic binder becomes relatively abundant in that area. As a result, molding defects occur, and the sintered body obtained by sintering the resulting molded body is accompanied by deterioration in surface properties such as deterioration in metallic luster and aesthetic appearance. [Means for solving the problem]

[0008] The injection molding composition according to the application example of the present invention is A titanium-based powder containing titanium as a main component and having an average particle size of 15 μm or more and 35 μm or less; Ceramics that are primarily made of ceramics and have an average grain size of 1 nm to 100 nm Powder and An organic binder; Including An injection molding composition comprising: Ratio of the ceramic powder to the total of the titanium-based powder and the ceramic powder The percentage is 0.01% by mass or more and 0.30% by mass or less, The melt viscosity at a measurement weight of 100 g, a measurement temperature of 150°C, and a measurement speed of 100 mm / min is Between 50 Pa s and 100 Pa s It is characterized by:

[0009] A method for producing an injection molded article according to an application example of the present invention includes the steps of: Titanium-based powder, ceramic, whose main component is titanium and whose average particle size is 15μm or more and 35μm or less. Ceramic powder with a mix as the main material and an average particle size of 1 nm to 100 nm. and an organic binder to obtain an injection molding composition; A step of obtaining an injection molded article by injection molding the injection molding composition; Have death, Ratio of the ceramic powder to the total of the titanium-based powder and the ceramic powder The percentage is 0.01% by mass or more and 0.30% by mass or less, The injection molding composition was measured at a weight of 100 g, a temperature of 150° C., and a speed of 100 mm. / min has a melt viscosity of 50 Pa·s or more and 100 Pa·s or less Characterized by .

[0010] A method for producing a titanium sintered body according to an embodiment of the present invention includes the steps of: A step of degreasing the injection molded body according to the application example of the present invention to obtain a degreased body; sintering the degreased body to obtain a sintered body; The present invention is characterized by having the following. [Brief description of the drawings]

[0011] [Figure 1] 1A to 1C are process diagrams illustrating a method for producing an injection molded article according to an embodiment. [Diagram 2] 2 is an enlarged cross-sectional view showing a mixed powder of titanium-based powder and ceramic powder obtained in the mixing step shown in FIG. 1. [Diagram 3] FIG. 3 is an enlarged view of part A in FIG. 2. [Figure 4] FIG. 4 is a cross-sectional view showing a state in which the amount of ceramic particles shown in FIG. 3 added is excessive. [Diagram 5] 1A to 1C are process diagrams showing a method for producing a titanium sintered body according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The injection molding composition, the method for producing an injection molded article, and the method for producing a titanium sintered article of the present invention will be described in detail below with reference to the accompanying drawings.

[0013] 1. Injection molding composition First, the injection molding composition according to the embodiment will be described.

[0014] The injection molding composition according to the embodiment is a molding material to be subjected to metal powder injection molding, and contains a titanium-based powder, a ceramic powder, and an organic binder.

[0015] Titanium-based powder is a powder whose main component is titanium and whose average particle size is 15 μm to 35 μm.Ceramic powder is a powder whose main material is ceramics and whose average particle size is 1 nm to 100 nm.

[0016] In such an injection molding composition, when the titanium-based powder and the ceramic powder are mixed, the ceramic powder particles are interposed between the titanium-based powder particles. This solves the problem that the titanium-based powder and the organic binder are difficult to mix. Specifically, ceramic powder particles having a smaller diameter than the titanium-based powder particles are distributed on the surface of the titanium-based powder particles. This makes it easier for the ceramic powder particles to slide between the titanium-based powder particles and the organic binder, increasing the fluidity of each, and making it easier for the titanium-based powder and the organic binder to mix uniformly. In addition, the ceramic powder is interposed between the titanium-based powder particles, reducing frictional resistance, which also contributes to improving the ease of mixing. As a result, a more homogeneous injection molding composition is obtained.

[0017] Furthermore, a homogeneous injection molding composition suppresses the occurrence of molding defects due to uneven distribution of the organic binder, which makes it possible to obtain an injection molded article with excellent surface properties, and ultimately to manufacture a titanium sintered body with excellent surface properties.

[0018] 1.1.Composition 1.1.1.Titanium-based powder The titanium-based powder contained in the injection molding composition is a powder containing titanium as a main component and having an average particle size of 15 μm or more and 35 μm or less.

[0019] Examples of the constituent material of the titanium-based powder include titanium itself and titanium-based alloys.

[0020] Titanium-based alloys are alloys whose main component is titanium, but which also contain elements other than titanium (Ti), such as carbon (C), nitrogen (N), oxygen (O), aluminum (Al), vanadium (V), niobium (Nb), zirconium (Zr), tantalum (Ta), molybdenum (Mo), chromium (Cr), manganese (Mn), cobalt (Co), iron (Fe), silicon (Si), gallium (Ga), tin (Sn), barium (Ba), nickel (Ni), and sulfur (S).

[0021] Specific compositions of titanium-based alloys include those specified as 60, 60E, 61, or 61F in JIS H 4600:2012. Specific examples include Ti-6Al-4V, Ti-6Al-4V ELI, and Ti-3Al-2.5V. Other examples include Ti-6Al-6V-2Sn, Ti-6Al-2Sn-4Zr-2Mo-0.08Si, and Ti-6Al-2Sn-4Zr-6Mo, which are specified in the Aerospace Materials Standard (AMS). In addition, examples include Ti-5Al-2.5Fe and Ti-6Al-7Nb, which are specified in the standard established by the International Organization for Standardization (ISO). Furthermore, examples include Ti-13Zr-13Ta, Ti-6Al-2Nb-1Ta, Ti-15Zr-4Nb-4Ta, and Ti-5Al-3Mo-4Zr.

[0022] The above alloy composition notation is written from the left with the highest concentration, and the number in front of the element is the concentration of that element expressed in mass%. For example, Ti-6Al-4V indicates that it contains 6 mass% Al and 4 mass% V, with the remainder being Ti and impurities. Note that impurities refer to elements that are unavoidably mixed in with a total concentration of 0.40 mass% or less, or elements that are intentionally added.

[0023] The details of the main alloy composition are as follows: The Ti-6Al-4V alloy contains 5.5% to 6.75% by mass of Al, 3.5% to 4.5% by mass of V, and the remainder being Ti and impurities. As impurities, for example, Fe is allowed to be contained in an amount of 0.4% by mass or less, O is allowed to be contained in an amount of 0.2% by mass or less, N is allowed to be contained in an amount of 0.05% by mass or less, H (hydrogen) is allowed to be contained in an amount of 0.015% by mass or less, and C is allowed to be contained in an amount of 0.08% by mass or less. Furthermore, other elements are allowed to be contained in an amount of 0.10% by mass or less individually, and 0.40% by mass or less in total.

[0024] The Ti-6Al-4V ELI alloy contains 5.5% to 6.5% by mass of Al, 3.5% to 4.5% by mass of V, and the remainder being Ti and impurities. As impurities, for example, Fe is permitted to be contained in an amount of 0.25% by mass or less, O is permitted to be contained in an amount of 0.13% by mass or less, N is permitted to be contained in an amount of 0.03% by mass or less, H is permitted to be contained in an amount of 0.0125% by mass or less, and C is permitted to be contained in an amount of 0.08% by mass or less. Furthermore, other elements are permitted to be contained in an amount of 0.10% by mass or less individually and 0.40% by mass or less in total.

[0025] The Ti-3Al-2.5V alloy contains Al in an amount of 2.5% by mass or more and 3.5% by mass or less, V in an amount of 1.6% by mass or more and 3.4% by mass or less, S in an amount of 0.05% by mass or more and 0.20% by mass or less as required, at least one of La (lanthanum), Ce (cerium), Pr (praseodymium) and Nd (neodymium) in a total amount of 0.05% by mass or more and 0.70% by mass or less as required, and the balance is Ti and impurities. As impurities, for example, Fe is allowed to be contained in an amount of 0.30% by mass or less, O is allowed to be contained in an amount of 0.25% by mass or less, N is allowed to be contained in an amount of 0.05% by mass or less, H is allowed to be contained in an amount of 0.015% by mass or less, and C is allowed to be contained in an amount of 0.10% by mass or less. Furthermore, other elements are allowed to be contained in an amount of 0.40% by mass or less in total.

[0026] The Ti-5Al-2.5Fe alloy contains 4.5% by mass or more and 5.5% by mass or less of Al, 2.0% by mass or more and 3.0% by mass or less of Fe, and the balance being Ti and impurities. As impurities, for example, O is allowed to be contained in an amount of 0.2% by mass or less, N is allowed to be contained in an amount of 0.05% by mass or less, H is allowed to be contained in an amount of 0.013% by mass or less, and C is allowed to be contained in an amount of 0.08% by mass or less. Furthermore, other elements are allowed to be contained in an amount of 0.40% by mass or less in total.

[0027] The Ti-6Al-7Nb alloy contains 5.5% by mass or more and 6.5% by mass or less of Al, 6.5% by mass or more and 7.5% by mass or less of Nb, and the remainder is Ti and impurities. As impurities, for example, Ta is allowed to be contained in an amount of 0.50% by mass or less, Fe is allowed to be contained in an amount of 0.25% by mass or less, O is allowed to be contained in an amount of 0.20% by mass or less, N is allowed to be contained in an amount of 0.05% by mass or less, H is allowed to be contained in an amount of 0.009% by mass or less, and C is allowed to be contained in an amount of 0.08% by mass or less. Furthermore, other elements are allowed to be contained in an amount of 0.40% by mass or less in total.

[0028] Furthermore, the components contained in the titanium-based powder can be analyzed by a method conforming to the titanium-ICP optical emission spectrometry method specified in, for example, JIS H 1632-1:2014 to JIS H 1632-3:2014.

[0029] As described above, the average particle size of the titanium-based powder is from 15 μm to 35 μm, preferably from 18 μm to 32 μm, and more preferably from 20 μm to 30 μm.

[0030] If the average particle size of the titanium-based powder is below the lower limit, the rolling property of the titanium-based powder particles is likely to decrease, and the flowability of the injection molding composition may decrease. If the average particle size of the titanium-based powder is above the upper limit, the particles of the titanium-based powder become large, and depending on the molding shape, the filling property into the mold may decrease.

[0031] The average particle size of the titanium-based powder is measured as follows. First, the injection molding composition is observed at a magnification of 100 times or more. Then, in the observed image, the area of ​​the particle image of the titanium-based powder is measured. Next, the diameter of a perfect circle having the same area as that area is determined. The determined diameter is regarded as the particle size of that particle image. In this manner, the particle sizes of 10 or more particle images are determined, and the average value is calculated. The calculated average value is regarded as the average particle size of the titanium-based powder.

[0032] Furthermore, when the constituent material of the titanium-based powder is a titanium-based alloy, the titanium-based powder may be a powder (prealloy powder) consisting of particles of a single alloy composition, or a mixed powder (premix powder) consisting of a mixture of multiple types of particles having different compositions.

[0033] 1.1.2.Ceramic powder The ceramic powder contained in the injection molding composition is a powder containing ceramic as a main material and having an average particle size of 1 nm or more and 100 nm or less.

[0034] Examples of ceramics include oxide-based ceramics such as aluminum oxide, magnesium oxide, titanium oxide, zirconium oxide, silicon oxide, iron oxide, potassium oxide, sodium oxide, calcium oxide, chromium oxide, and niobium oxide; nitride-based ceramics such as boron nitride and silicon nitride; and silicon carbide. One or more of these may be used.

[0035] Of these, the ceramic is preferably an oxide-based ceramic containing an oxide as a main component, and the standard free energy of formation of the oxide at 1000°C is preferably lower than the standard free energy of formation of titanium oxide at 1000°C.

[0036] As a result, when the injection molding composition is molded and sintered, the titanium contained in the titanium-based powder reduces the oxides contained in the ceramic powder. As a result, the ceramic powder is less likely to remain as it is in the titanium sintered body. In other words, when the oxides are reduced to simple metals or simple nonmetals, they are highly likely to be dissolved in the matrix of the titanium sintered body. On the other hand, if the ceramic powder remains as it is, it may exist as inclusions in the titanium sintered body depending on the ceramic composition. Such inclusions may hinder the increase in sintering density of the titanium sintered body or reduce the mechanical properties.

[0037] Therefore, by using an oxide ceramic having the above-mentioned standard free energy of formation, it is possible to obtain an injection molding composition capable of producing a titanium sintered body having excellent surface properties and mechanical properties.

[0038] The oxide is preferably silicon oxide. When silicon oxide is reduced by titanium, it produces silicon. When silicon is dissolved in the matrix of the titanium sintered body, it contributes to improving mechanical properties such as tensile strength and does not adversely affect the surface properties of the titanium sintered body. Silicon oxide powder is relatively easy to obtain and inexpensive.

[0039] As described above, the average particle size of the ceramic powder is 1 nm or more and 100 nm or less, preferably 3 nm or more and 50 nm or less, more preferably 5 nm or more and 20 nm or less. If the average particle size of the ceramic powder is within the above range, the ceramic powder is easily distributed on the particle surface of the titanium-based powder. Then, the ceramic powder particles distributed on the particle surface of the titanium-based powder roll, and the slip between the titanium-based powder particles and the organic binder can be enhanced. In addition, the slip between the titanium-based powder particles is also improved. As a result, the fluidity of the injection molding composition can be increased. In addition, even if the ceramic powder remains in the titanium sintered body, the particle size of the inclusions is sufficiently small, so that the influence on the surface properties and mechanical properties of the titanium sintered body can be minimized.

[0040] If the average particle size of the ceramic powder is below the lower limit, the particles of the ceramic powder will not easily roll. Therefore, the above-mentioned effect may not be obtained. On the other hand, if the average particle size of the ceramic powder is above the upper limit, inclusions derived from the ceramic powder may easily hinder the sintering of the injection molding composition, or even if the ceramic is reduced by titanium, some of the ceramic may remain, which may deteriorate the surface properties of the titanium sintered body.

[0041] The average particle size of the ceramic powder is preferably 0.01% to 0.50% of the average particle size of the titanium-based powder, more preferably 0.02% to 0.40%, and even more preferably 0.03% to 0.30%.

[0042] This makes it possible to obtain an injection molding composition that can improve both the surface properties and mechanical properties of the titanium sintered body.

[0043] The ratio of the ceramic powder in the total of the titanium-based powder and the ceramic powder is not particularly limited, but is preferably 0.01% by mass or more and 0.30% by mass or less, more preferably 0.02% by mass or more and 0.20% by mass or less, and even more preferably 0.03% by mass or more and 0.15% by mass or less. By setting the ratio of the ceramic powder within the above range, the effect of adding the ceramic powder can be fully enjoyed, and the influence of inclusions derived from the ceramic powder can be minimized. In addition, particularly when oxide-based ceramics are used, it is easy to suppress the remaining inclusions.

[0044] If the ratio of the ceramic powder is below the lower limit, the effect of adding the ceramic powder may not be fully obtained, whereas if the ratio of the ceramic powder is above the upper limit, the injection molded body may be prone to molding defects, and the surface properties and mechanical properties of the titanium sintered body may be deteriorated.

[0045] The average particle size of the ceramic powder is measured in the same manner as the average particle size of the titanium-based powder.

[0046] The ceramic powder may be surface-treated as necessary. Examples of surface treatments include hydrophobic treatment, coupling agent treatment, and organosilazane treatment. By subjecting the ceramic powder to hydrophobic treatment, the adsorption of moisture to the ceramic powder is suppressed. Therefore, the occurrence of aggregation in the ceramic powder can be further suppressed. By subjecting the ceramic powder to coupling agent treatment or organosilazane treatment, characteristics according to the functional groups contained in the coupling agent or organosilazane can be imparted. For example, the affinity between the ceramic powder and the organic binder can be increased, the hydrophobicity of the ceramic powder can be increased, and the aggregation of the ceramic powder can be suppressed.

[0047] The hydrophobic treatment may be, for example, trimethylsilylation, arylations such as phenylation, etc. For trimethylsilylation, a trimethylsilylating agent such as trimethylchlorosilane is used. For arylation, an arylating agent such as an aryl halide is used.

[0048] The coupling agent treatment may be, for example, a treatment using a coupling agent containing an alkyl group, a methacryl group, an epoxy group, an amino group, a vinyl group, a phenyl group, or a mercapto group as a functional group.

[0049] The organosilazane treatment may be, for example, a treatment using an organosilazane such as tetramethyldisilazane, hexamethyldisilazane, or pentamethyldisilazane.

[0050] 1.1.3.Organic binders The content of the organic binder in the injection molding composition is appropriately set according to the molding conditions and the shape to be molded, but is preferably about 2% by mass to 20% by mass, more preferably about 5% by mass to 10% by mass of the injection molding composition. By setting the content of the organic binder within the above range, the injection molding composition has good fluidity. This improves the filling property of the injection molding composition during molding, and finally, a titanium sintered body having a shape closer to the desired shape can be obtained.

[0051] Examples of the organic binder include polyolefins such as polyethylene, polypropylene, and ethylene-vinyl acetate copolymers; acrylic resins such as polymethyl methacrylate and polybutyl methacrylate; styrene resins such as polystyrene; polyesters such as polyvinyl chloride, polyvinylidene chloride, polyamide, polyethylene terephthalate and polybutylene terephthalate; polyethers, polyvinyl alcohols, polyvinylpyrrolidone, and copolymers thereof; and various organic binders such as various waxes, paraffins, higher fatty acids, higher alcohols, higher fatty acid esters, and higher fatty acid amides. These can be used alone or in combination of two or more.

[0052] 1.1.4. Additives If necessary, the injection molding composition may contain a plasticizer, such as phthalic acid ester, adipic acid ester, trimellitic acid ester, sebacic acid ester, etc., which may be used alone or in combination of two or more.

[0053] Furthermore, in addition to the titanium-based powder, organic binder, and plasticizer, various additives such as lubricants, antioxidants, degreasing accelerators, and surfactants can be added to the injection molding composition as necessary.

[0054] The content of the additive in the injection molding composition is preferably 10.0% by mass or less, and more preferably 5.0% by mass or less.

[0055] 1.2.Physical Properties As described above, the injection molding composition according to the embodiment has improved fluidity due to the addition of the ceramic powder. The melt viscosity of the injection molding composition is one factor in improving the fluidity.

[0056] The melt viscosity of the injection molding composition at a measurement weight of 100 g, a measurement temperature of 150° C., and a measurement speed of 100 mm / min is preferably 500 Poise to 1000 Poise, and more preferably 600 Poise to 900 Poise. By keeping the melt viscosity of the injection molding composition within the above range, the occurrence of molding defects due to uneven distribution of the organic binder during injection molding is suppressed, regardless of the shape of the mold.

[0057] The melt viscosity of the injection molding composition is measured, for example, by a melt viscosity measuring device, Capillograph 1B, manufactured by Toyo Seiki Seisakusho, Ltd.

[0058] 2. Manufacturing method of injection molded products Next, a method for producing an injection molded article according to an embodiment will be described. FIG. 1 is a process diagram showing a method for producing an injection molded article according to an embodiment.

[0059] The method for producing an injection molded article shown in FIG. 1 includes a mixing step S102 and an injection molding step S104.

[0060] 2.1.Mixing process In the mixing step S102, the titanium-based powder, the ceramic powder, and the organic binder are mixed together.

[0061] The order of mixing is not particularly limited, but preferably, first, the titanium-based powder and the ceramic powder are mixed to obtain a mixed powder. That is, prior to mixing with the organic binder, the two types of powder are mixed in advance to obtain a premixed powder. A known mixer is used for this mixing. In addition, the mixing is preferably performed in a dry state (dry blend). The dry state refers to a state in which the mixed powder does not contain a liquid that exists independently, that is, a state in which the mixed powder does not contain a liquid that exists without being adsorbed on the surface of the particles of the titanium-based powder and the ceramic powder. By mixing in such a state, aggregation of the ceramic powder due to the liquid is suppressed, and the titanium-based powder and the ceramic powder can be mixed more uniformly.

[0062] Fig. 2 is an enlarged cross-sectional view of the mixed powder of titanium-based powder and ceramic powder obtained in the mixing step S102 shown in Fig. 1. Fig. 3 is an enlarged view of part A in Fig. 2. In the following description, the particles of the titanium-based powder are referred to as "titanium particles 2" and the particles of the ceramic powder are referred to as "ceramic particles 3."

[0063] As shown in Figures 2 and 3, in the mixed powder, ceramic particles 3 are interposed between titanium particles 2. This allows the ceramic particles 3 to act like rollers between the titanium particles 2. As a result, the ceramic particles 3 prevent adjacent titanium particles 2 from interfering with each other's rolling. This increases the fluidity of the titanium particles 2 and the ceramic particles 3, resulting in a homogeneous mixed powder.

[0064] In order for the ceramic particles 3 to act like rollers, it is preferable that a single layer of the ceramic particles 3 is interposed between the titanium particles 2 as shown in Fig. 3. This makes it particularly easy for the ceramic particles 3 to roll along the surfaces of the adjacent titanium particles 2.

[0065] In order for the ceramic particles 3 to act as described above, it is preferable to set the amount of the ceramic particles 3 added within the above-mentioned range. By optimizing the amount of the ceramic particles 3 added, the state shown in FIG. 3 can be easily realized.

[0066] If the ratio of ceramic powder is below the lower limit, the above effect may not be fully achieved, and if the ratio of ceramic powder exceeds the upper limit, the ceramic particles 3 will be stacked in multiple layers between the titanium particles 2.

[0067] Fig. 4 is a cross-sectional view showing a state in which the amount of ceramic particles 3 added shown in Fig. 3 is excessive. In other words, Fig. 4 shows a state in which the amount of ceramic particles 3 added exceeds the upper limit.

[0068] When an excessive amount of ceramic particles 3 is added, the ceramic particles 3 interposed between the titanium particles 2 are piled up in multiple layers as shown in Fig. 4. Therefore, the ceramic particles 3 are difficult to roll due to frictional resistance between the ceramic particles 3. As a result, depending on the particle size of the titanium particles 2 and the particle size of the ceramic particles 3, it may be difficult to increase the fluidity of the titanium particles 2 and the ceramic particles 3.

[0069] Next, the resulting mixed powder is mixed with an organic binder and kneaded to obtain an injection molding composition.

[0070] The injection molding composition may be a mixture, or may be a kneaded product obtained by kneading the mixture as described above. The kneading conditions vary depending on the particle size of the titanium-based powder used, the particle size and amount of the ceramic powder added, the composition and amount of the organic binder added, etc., but an example of the kneading conditions is a kneading temperature of about 50°C to 200°C, and a kneading time of about 15 minutes to 210 minutes.

[0071] The injection molding composition may be formed into pellets (small lumps) as needed. The pellets may have a particle size of, for example, about 1 mm or more and 15 mm or less.

[0072] 2.2. Injection molding process In the injection molding step S104, the resulting kneaded product is injection molded to obtain an injection molded body.

[0073] Metal injection molding (MIM) is used for molding. The injection molding conditions vary depending on the particle size of the titanium powder used, the particle size and amount of ceramic powder added, the composition and amount of organic binder added, etc., but one example is a material temperature of 80°C to 210°C, and an injection pressure of 50 MPa to 500 MPa (0.5 t / cm). 2 More than 5t / cm 2 It is preferable that the temperature is about 100° C. or less.

[0074] The shape and dimensions of the injection molded body are determined taking into account the shrinkage of the injection molded body during the debinding and sintering steps described below.

[0075] If necessary, the injection molded body may be subjected to machining such as cutting, polishing, cutting, etc. The injection molded body is easier to process than the titanium sintered body.

[0076] As described above, the manufacturing method of the injection molded body according to the present embodiment includes a mixing step S102 and an injection molding step S104. In the mixing step S102, a titanium-based powder, a ceramic powder, and an organic binder are mixed to obtain an injection molding composition. The titanium-based powder is a powder containing titanium as a main component and having an average particle size of 15 μm to 35 μm. The ceramic powder is a powder containing ceramics as a main material and having an average particle size of 1 nm to 100 nm. In the injection molding step S104, the injection molding composition is injection molded to obtain an injection molded body.

[0077] According to this configuration, when the titanium-based powder and the ceramic powder are mixed in the mixing step S102, the ceramic powder particles are interposed between the titanium-based powder particles. This solves the problem that the titanium-based powder and the organic binder are difficult to mix. In addition, the ceramic powder is interposed between the titanium-based powder particles, which reduces frictional resistance and contributes to improving the ease of mixing. As a result, a more homogeneous injection molding composition is obtained.

[0078] Furthermore, a homogeneous injection molding composition suppresses the occurrence of molding defects due to uneven distribution of the organic binder, which makes it possible to obtain an injection molded article with excellent surface properties, and ultimately to manufacture a titanium sintered body with excellent surface properties.

[0079] 3. Manufacturing method of titanium sintered body Next, a method for producing a titanium sintered body according to an embodiment will be described. FIG. 5 is a process diagram showing the method for producing a titanium sintered body according to the embodiment.

[0080] The method for producing a titanium sintered body shown in FIG. 5 includes a degreasing step S106 and a sintering step S108.

[0081] 3.1. Degreasing process In the degreasing step S106, the obtained injection molded body is subjected to a degreasing treatment to remove at least a part of the organic binder, thereby obtaining a degreased body.

[0082] Examples of the degreasing treatment include a method of heating the injection molded article and a method of exposing the injection molded article to a gas that decomposes the binder.

[0083] When the method of heating the injection molded body is used, the heating conditions of the injection molded body vary slightly depending on the composition and amount of the organic binder, but are preferably a heating temperature of 100° C. to 750° C. and a heating time of about 0.1 to 20 hours, and more preferably a heating temperature of 150° C. to 600° C. and a heating time of about 0.5 to 15 hours. This allows the injection molded body to be degreased necessary and sufficiently without being sintered or deformed.

[0084] The atmosphere for the degreasing treatment is not particularly limited, and examples thereof include a reducing gas atmosphere such as hydrogen, an inert gas atmosphere such as nitrogen or argon, an oxidizing gas atmosphere such as air, or a reduced pressure atmosphere obtained by reducing the pressure of these atmospheres, etc. Among these, an inert gas atmosphere or a reduced pressure atmosphere is preferably used from the viewpoint of suppressing oxidation of titanium.

[0085] On the other hand, examples of gases that decompose the binder include ozone gas. Furthermore, by carrying out such a degreasing process in multiple steps with different degreasing conditions, the organic binder in the injection-molded body can be degreased more quickly and without deforming the injection-molded body.

[0086] If necessary, the degreased body may be subjected to mechanical processing such as cutting, polishing, cutting, etc. The degreased body is easier to process than the titanium sintered body.

[0087] 3.2.Sintering process In the sintering step S108, the obtained degreased body is sintered in a sintering furnace to obtain a sintered body. This causes diffusion at the interfaces between the particles of the titanium-based powder, leading to sintering. As a result, a titanium sintered body is obtained.

[0088] The firing temperature varies depending on the composition and particle size of the titanium-based powder, but is, for example, about 900° C. to 1400° C., and preferably about 1050° C. to 1300° C.

[0089] The firing time is set to be 0.2 hours or more and 7 hours or less, and preferably 1 hour or more and 6 hours or less.

[0090] The sintering atmosphere is not particularly limited, but in consideration of preventing significant oxidation of the metal powder, a reducing gas atmosphere such as hydrogen, an inert gas atmosphere such as nitrogen or argon, or a reduced pressure atmosphere obtained by reducing the pressure of these atmospheres is preferably used.

[0091] In the sintering step, the firing temperature or the firing atmosphere, which will be described later, may be changed midway.

[0092] As described above, the method for producing a titanium sintered body according to this embodiment includes the degreasing step S106 and the sintering step S108. In the degreasing step S106, the injection molded body is degreased to obtain a degreased body. In the sintering step S108, the degreased body is sintered to obtain a sintered body.

[0093] According to this configuration, the occurrence of molding defects due to uneven distribution of the organic binder in the injection molded body is suppressed, and therefore the occurrence of low density parts due to molding defects is suppressed, and a titanium sintered body with excellent surface properties can be obtained.

[0094] 3.3. Post-process The titanium sintered body obtained as described above may be subjected to post-treatment as necessary. The post-treatment is not particularly limited, but examples thereof include HIP treatment (hot isostatic pressing), polishing, etc. Among these, the HIP treatment can further increase the density of the titanium sintered body and further improve the mechanical properties.

[0095] The conditions for the HIP treatment include, for example, a heating temperature of 850° C. to 1200° C. and a heating time of 1 hour to 10 hours. The applied pressure is preferably 50 MPa or more, and more preferably 100 MPa to 500 MPa.

[0096] Examples of the polishing treatment include electrolytic polishing, buff polishing, dry polishing, chemical polishing, barrel polishing, sandblasting, etc. By carrying out these polishing treatments, it is possible to impart metallic luster to the surface of the titanium sintered body and to enhance the specularity. Furthermore, by enhancing the specularity, the sliding resistance of the surface of the titanium sintered body is reduced, and the wear resistance of the titanium sintered body can be enhanced.

[0097] The injection molding composition, the method for producing an injection molded body, and the method for producing a titanium sintered body of the present invention have been described above based on preferred embodiments, but the present invention is not limited thereto. For example, the mixing step may include an operation of mixing a composition containing a titanium-based powder and an organic binder with a composition containing a ceramic powder and an organic binder. In addition, the method for producing an injection molded body and the method for producing a titanium sintered body of the present invention may be one in which any purposed step is added to the above-mentioned embodiments. EXAMPLES

[0098] Next, specific examples of the present invention will be described. 4. Manufacturing of titanium sintered body Example 1 4.1.1.Mixing process First, a pure Ti powder having an average particle size of 23 μm produced by gas atomization was prepared as the titanium-based powder. The titanium concentration of the pure Ti powder was 99 mass % or more.

[0099] In addition, silicon oxide powder (silica powder) with an average particle size of 10 nm was prepared as the ceramic powder. The main material of the silica powder is silicon oxide (SiO or SiO2).

[0100] In addition, a mixture of polypropylene and paraffin wax was prepared as an organic binder. The ratio of the total mass of the titanium-based powder and ceramic powder to the mass of the organic binder was 9:1.

[0101] Next, the titanium-based powder and the ceramic powder were mixed in a mixer to obtain a mixed powder. Next, the obtained mixed powder and an organic binder were kneaded in a kneader to obtain an injection molding composition, which was then processed into pellets.

[0102] 4.1.2. Injection molding process Next, the obtained pellets were injection molded under the molding conditions shown below to obtain an injection molded article.

[0103] ·Molding method: Metal powder injection molding method ·Material temperature: 150℃

[0104] 4.1.3. Degreasing process Next, the obtained injection molded body was subjected to a degreasing treatment under the degreasing conditions shown below to obtain a degreased body.

[0105] Degreasing temperature: 520℃ Heating time for degreasing: 5 hours Degreasing atmosphere: Nitrogen gas atmosphere

[0106] 4.1.4.Sintering process Next, the obtained degreased body was sintered under the firing conditions shown below to obtain a titanium sintered body. The above production conditions are shown in Table 1.

[0107] 4.2. Examples 2 to 31 A titanium sintered body was obtained in the same manner as in Example 1, except that the production conditions were changed as shown in Tables 1 to 3. Note that "all-in-one mixing" in each table refers to a mixing method in which the titanium-based powder, ceramic powder, and organic binder are all mixed together in the mixing step.

[0108] 4.3. Comparative Examples 1 to 12 Titanium sintered bodies were obtained in the same manner as in the Examples, except that the production conditions were changed as shown in Tables 1 to 3. In Comparative Examples 1, 5, and 9, the addition of ceramic powder was omitted.

[0109] 4.4.Reference examples 1~3 An ingot material of pure Ti was prepared as Reference Example 1. An ingot material of Ti-6Al-4V alloy was prepared as Reference Example 2. Furthermore, an ingot material of Ti-6Al-7Nb alloy was prepared as Reference Example 3.

[0110] 5. Evaluation of titanium sintered body 5.1.Evaluation of surface properties The surface properties of the titanium sintered bodies of the Examples and Comparative Examples were observed with an optical microscope. The results of the observation of the surface properties were evaluated in accordance with the following evaluation criteria.

[0111] A: The surface quality is very good (particularly the aesthetic appearance is excellent). B: Surface quality is somewhat good (aesthetic appearance is somewhat excellent) C: The surface quality is somewhat poor (the aesthetic appearance is somewhat poor) D: The surface quality is very poor (particularly poor aesthetic appearance). The evaluation results are shown in Tables 1 to 3.

[0112] 5.2.Evaluation of mechanical strength The tensile strength of the titanium sintered body of each Example and Comparative Example and the ingot titanium material of the Reference Example was measured in accordance with the tensile test method for metallic materials specified in JIS Z 2241:2011.

[0113] Next, the tensile strengths obtained for the ingot titanium materials of Reference Examples 1 to 3 were set as reference value 1, and the relative values ​​of the tensile strengths obtained for the ingot titanium materials of each Example and Comparative Example were calculated. Note that the calculation of the relative values ​​was performed using the tensile strength of Reference Example 1 as the reference value in Table 1, the tensile strength of Reference Example 2 as the reference value in Table 2, and the tensile strength of Reference Example 3 as the reference value in Table 3. The obtained relative values ​​were evaluated against the following evaluation criteria.

[0114] A: Relative value of tensile strength is 1.00 or more (same as or better than ingot material) B: The relative value of tensile strength is 0.97 or more and less than 1.00 C: Relative value of tensile strength is 0.94 or more and less than 0.97 D: Relative value of tensile strength is 0.91 or more and less than 0.94 E: Relative value of tensile strength is 0.88 or more and less than 0.91 F: Relative value of tensile strength is less than 0.88 The evaluation results are shown in Tables 1 to 3.

[0115] [Table 1]

[0116] [Table 2]

[0117] [Table 3]

[0118] As is clear from Tables 1 to 3, the titanium sintered bodies of the Examples had better surface properties than the titanium sintered bodies of the Comparative Examples. Therefore, the titanium sintered bodies of the Examples have excellent aesthetic appearance and are preferably used for various purposes.

[0119] Moreover, the tensile strength of the titanium sintered bodies of the Examples was equal to or greater than that of the titanium sintered bodies of the Comparative Examples. [Explanation of symbols]

[0120] 2...Titanium particles, 3...Ceramic particles, S102...Mixing process, S104...Injection molding process, S106...Degreasing process, S108...Sintering process

Claims

1. a titanium-based powder containing titanium as a main component and having an average particle size of 15 μm or more and 35 μm or less; Ceramics that are primarily made of ceramics and have an average grain size of 1 nm or more and 100 nm or less Powder, An organic binder; An injection molding composition comprising: Ratio of the ceramic powder to the total of the titanium-based powder and the ceramic powder The ratio is 0.01% by mass or more and 0.30% by mass or less, The melt viscosity at a measurement weight of 100 g, a measurement temperature of 150° C., and a measurement speed of 100 mm / min is An injection molding composition having a viscosity of 50 Pa·s or more and 100 Pa·s or less.

2. The ceramic is an oxide-based ceramic containing an oxide as a main component, The standard free energy of formation of the oxide at 1000°C is 2. The injection molding composition of claim 1, wherein the standard free energy of formation is less than or equal to the standard free energy of formation at

3. 3. The injection molding composition according to claim 2, wherein the oxide is silicon oxide.

4. Titanium-based powder, ceramic, containing titanium as the main component and having an average particle size of 15 μm or more and 35 μm or less A ceramic powder containing a mix as a main material and having an average particle size of 1 nm or more and 100 nm or less; and an organic binder to obtain an injection molding composition; A step of obtaining an injection molded article by injection molding the injection molding composition; having Ratio of the ceramic powder to the total of the titanium-based powder and the ceramic powder The ratio is 0.01% by mass or more and 0.30% by mass or less, The injection molding composition was measured at a weight of 100 g, a temperature of 150° C., and a speed of 100 mm. / min is characterized in that the melt viscosity is 50 Pa s or more and 100 Pa s or less. A method for manufacturing an injection molded article.

5. A step of degreasing the injection molded body according to claim 4 to obtain a degreased body; sintering the degreased body to obtain a sintered body; A method for producing a titanium sintered body, comprising the steps of:

Citation Information

Patent Citations

  • Crown repair material

    JP1998201771A

  • Method for manufacturing finger ring member for scissors formed by metal powder injection molding method

    JP2009142594A

  • Method for manufacturing powder injection molded articles

    JP2011503361A

  • Process for producing a beta-alloy Titanium Niobium Zirconium (TNZ) with a very low modulus of elasticity for biomedical applications and its embodiment by additive manufacturing.

    US20190111482A1

  • Method of manufacturing high-density titanium alloy article

    US6325964B1